2016
DOI: 10.18632/oncotarget.7016
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin promotes epithelial-mesenchymal transition of hepatocellular carcinoma through regulating vimentin

Abstract: Our previous studies have found that osteopontin (OPN) is a promoter for hepatocellular carcinoma (HCC) progression. However, the molecular mechanism by which OPN enhances HCC metastasis remains elusive. Epithelial-mesenchymal transition (EMT) of cancer cells plays a pivotal role in promoting metastatic process. In this study, we demonstrated that OPN promotes HCC metastasis by inducing an EMT-like, more aggressive cellular phenotype in vitro and in vivo. Furthermore, OPN was identified to interact with viment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 36 publications
4
60
0
Order By: Relevance
“…5C, left panel). Surprisingly, two other targets of β-catenin, osteopontin [OPN; which is known as a master regulator of EMT (41) via its ability to stabilize vimentin (42)] and Axin2 [AXIN2, which enhances EMT via induction of Snail (43)] were not suppressed, and instead were increased in Daple-YE cells (Fig. 5C, right panel).…”
Section: Resultsmentioning
confidence: 99%
“…5C, left panel). Surprisingly, two other targets of β-catenin, osteopontin [OPN; which is known as a master regulator of EMT (41) via its ability to stabilize vimentin (42)] and Axin2 [AXIN2, which enhances EMT via induction of Snail (43)] were not suppressed, and instead were increased in Daple-YE cells (Fig. 5C, right panel).…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidence has demonstrated that OPN contributes to metastasis and poor prognosis of cancers, including HCC . Thus, understanding how OPN are involved in maintaining the aggressive phenotype of HCC cells may help to identify novel potential targets for HCC .…”
Section: Discussionmentioning
confidence: 99%
“…Human HCC tissue specimens were obtained following the guidelines approved by the Ethics Committee of the Liver Cancer Institute, Fudan University, and written informed consent was obtained from patients in all cases. Immunohistochemical (IHC) staining was performed as described previously . Briefly, tissue specimens were incubated using antibodies against OPN (1:200 dilution, Abcam, Cambridge, MA, USA), CCR1 (1:100 dilution, Novus, St. Louis, MO, USA) and a biotin‐conjugated secondary antibody and then incubated with an avidin‐biotin‐peroxidase complex.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4C, [24]) is totally abolished after vibration. Moreover, VIM which is often stabilized by OPN [25] is significantly reduced. This fact could contribute to enhanced stability of ICAM-1 [26].…”
Section: Quantitative Real-time Pcr (Qpcr) Of Selected Gravitationallmentioning
confidence: 99%